Grip strength after hamate hook excision and reconstruction surgery: A biomechanical cadaveric study. (August 2022) - Kuptniratsaikul, Vanasiri; Luangjarmekorn, Pobe; Kerr, Stephen; Vinitpairot, Chaiyos; Kitidumrongsook, Pravit
Abstract: Fractures of the hamate hook are common among professional athletes. The recommended treatment for this is hamate hook excision. The purpose of this study is to evaluate the hand grip strength after hamate hook resection at different levels. Six cadaver forearm flexor digitorum profundus tendons were loaded with 5- to 15-kilograms force and grip strength was subsequently measured. The same measurements were performed in five hamate hook conditions: normal, one-third, two-thirds, total hamate excision, and after perihamate ligament reconstruction. Multilevel mixed-effect models were used to calculate the scaling ratios after each surgical intervention and compared them to a normal hamate hook. A 25%, 36%, 47% reduction, and 7% increase (107% of baseline) in grip strength was found after one-third, two-thirds, total bone was resected, and after perihamate ligament reconstruction, respectively. The study shows an association between grip strength reduction and the level of hamate hook resection. Perihamate ligament reconstruction is recommended as it restores grip strength to normal.